2001
DOI: 10.1038/sj.onc.1204440
|View full text |Cite
|
Sign up to set email alerts
|

p21 Waf1/Cip1 can protect human colon carcinoma cells against p53-dependent and p53-independent apoptosis induced by natural chemopreventive and therapeutic agents

Abstract: The molecular basis for the sensitivity of tumor cells to chemopreventive natural food compounds and commonly used chemotherapeutic agents is not well understood, not least because studies are frequently confounded by the diversity among cell lines or rely on experimental protein overexpression. Here we investigated the e ects of nbutyrate, a cancer-preventive short-chain fatty acid produced by anaerobic bacteria in the gastrointestinal tract, on the human wild-type p53 and p21 expressing HCT116 colon carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(115 citation statements)
references
References 54 publications
8
106
0
1
Order By: Relevance
“…A number of studies evaluating the impact of p21 WAF1 on cell death have been conducted in epithelial derived tumor cells such as MCF-7 or HCT116 cell lines. [6][7][8][9]46,47 In general, most of the tumor cell lines showed inherent resistance to the effects of certain cytotoxic stimuli. 7,46 Furthermore, enhanced apoptotic responses of p21 WAF1 -deficient HCT116 cells to DNA damage occurred after 24 h exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies evaluating the impact of p21 WAF1 on cell death have been conducted in epithelial derived tumor cells such as MCF-7 or HCT116 cell lines. [6][7][8][9]46,47 In general, most of the tumor cell lines showed inherent resistance to the effects of certain cytotoxic stimuli. 7,46 Furthermore, enhanced apoptotic responses of p21 WAF1 -deficient HCT116 cells to DNA damage occurred after 24 h exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9]46,47 In general, most of the tumor cell lines showed inherent resistance to the effects of certain cytotoxic stimuli. 7,46 Furthermore, enhanced apoptotic responses of p21 WAF1 -deficient HCT116 cells to DNA damage occurred after 24 h exposure. 9,46,47 Cell death was observed within 6 h after drug exposure in both T-ALL and BCP-ALL PDXs and cell lines, demonstrating the increased cytotoxic sensitivity of leukemia cells compared to epithelial derived cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…As a p53 transcriptional target, p21 is classically proposed to be under the regulation of the ATM-p53 pathway where it induces G1 arrest. Modulation of p21 expression and consequent apoptosis can also occur via p53-independent pathways (Mahyar-Roemer and Roemer, 2001). In fact, p21 expression in pancreatic carcinoma is independent of p53 status (DiGiuseppe et al, 1995).…”
Section: Dna Damage Induced Apoptosis and Role Of Chk1mentioning
confidence: 99%
“…However, the protective effect of p53 and p21 against resveratrol is not nearly as strong as that against doxorubicin. 10,21 Several studies have suggested that the chemopreventive activity of resveratrol is largely based on its proapoptotic effects. For instance, azomethane-induced colon carcinogenesis in rats appears to be counteracted by apoptosis of damaged cells.…”
Section: Epithelial Differentiation At Early Times During Resveratrolmentioning
confidence: 99%